Metastatic Salivary Gland Tumors: A Single-Center Study Demonstrating the Feasibility and Potential Clinical Benefit of Molecular-Profiling-Guided Therapy. (13th September 2015) - Popovtzer, Aron; Sarfaty, Michal; Limon, Dror; Marshack, Gideon; Perlow, Eli; Dvir, Addie; Soussan-Gutman, Lior; Stemmer, Salomon M.
Abstract : We evaluated the use of molecular profiling (MP) for metastatic salivary gland adenoid cystic carcinoma (SACC), for which there is no standard treatment. MP (Caris Molecular Intelligence) was performed on biopsy samples from all metastatic SACC patients attending a tertiary medical center between 2010 and 2013 n = 14 . Treatment was selected according to the biomarkers identified. Findings were compared with all similarly diagnosed patients treated in the same center between 1996 and 2009 n = 9 . For each patient, MP identified 1–13 biomarkers associated with clinical benefit for specific therapies (most commonly low/negative TS, low ERCC1). Eleven patients (79%) received MP-guided treatment (2 died prior to treatment initiation, 1 opted not to be treated), with complete response in 1, partial response (PR) in 3, and stable disease in 4. In the historical controls, 2 patients (22%) were treated (1 had PR). Median (range) progression-free survival in the first line after MP was 8.2 months (1.4–49.5+). Median (range) overall survival from diagnosis of metastatic disease was 31.3 (1.4–71.1+) versus 14.0 (1.5–116) months in the historical controls. In conclusion, MP expands treatment options and may improve clinical outcomes for metastatic SACC. In orphan diseases where randomized trials cannot be performed, MP could become a standard clinical tool.